Comparison of the gut microbiota profile in breast-fed and formula-fed Korean infants using pyrosequencing - Sang A Lee; Ji Ye Lim; Bong Soo Kim; Su Jin Cho; Nak Yon Kim; Ok Bin Kim; Yuri Kim (2015)
BACKGROUND/OBJECTIVES: Feeding in infancy is the most significant determinant of the intestinal microbiota in early life.The aim of this study was to determine the gut microbiota of Korean infants and compare the microbiota obtained between breast-fed and formula-fed Korean infants.SUBJECTS/METHODS: We analyzed the microbial communities in fecal samples collected from twenty 4-week old Korean (ten samples in each breast-fed or formula-fed) infants using pyrosequencing. RESULTS:The fecal microbiota of the 4-week-old Korean infants consisted of the three phyla Actinobacteria, Firmicutes, and Proteobacteria.In addition, five species, including Bifidocbacterium longum, Streptococcus salivarius, Strepotococcus lactarius, Streptococcus pseudopneumoniae, and Lactobacillus gasseri were common commensal intestinal microbiota in all infants.The predominant intestinal microbiota in the breast-fed infants (BFI) included the phylum Actinobacteria (average 70.55%), family Bifidobacteriacea (70.12%), genus Bifidobacterium (70.03%) and species Bifidobacterium longum (69.96%).In the microbiota from the formula-fed infants (FFI), the proportion of the phylum Actinobacteria (40.68%) was less, whereas the proportions of Firmicutes (45.38%) and Proteobacteria (13.85%) as well as the diversity of each taxonomic level were greater, compared to those of the BFI.The probiotic species found in the 4-week-old Korean infants were Bifidobacterium longum, Streptococcus salivarius, and Lactobacillus gasseri.These probiotic species accounted for 93.81% of the microbiota from the BFI, while only 63.80% of the microbiota from the FFI.In particular, B. longum was more abundant in BFI (69.96%) than in FFI (34.17%).CONCLUSIONS: Breast milk supports the growth of B. longum and inhibits others.To the best of our knowledge, this study was the first attempt to analyze the gut microbiota of healthy Korean infants according to the feeding type using pyrosequencing.Our data can be used as a basis for further studies to investigate the development of intestinal microbiota with aging and disease status.